EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED-LEARNING TERHADAP PEMAHAMAN HAK DAN KEWAJIBAN WARGA NEGARA PADA SISWA KELAS X DI SMA NEGERI 5 TUBAN - Nilna Izza Bella; Mardi Widodo (Jurnal Binagogik, 2025)
The study aims to examine the problem-based learning method for the tenthgrade students of SMA Negeri 5 Tuban in the Pancasila Education subject. The background is based on field facts with the PBL method being very efficient and active and fostering critical thinking in students. For this study, a quantitative approach using the quasi-experimental Non-Equivalent Control Group Design method was used. Pre-test and post-test were designed for two experimental and control groups with 36 samples each. Where the experimental group used the PBL method and the control group used the conventional method. Data collection through tests and documentation, validity tests, normality tests, and t-tests were used. The results showed that the use of PBL was able to have a significant impact on students' understanding in the learning process. According to statistical analysis, a significant value of >0.05 was obtained, accepting that there were significant differences between the PBL and conventional methods in the material of citizens' rights and obligations. It is hoped that the results of this study will contribute to the development of interactive learning models in teaching Pancasila Education and help teachers choose methods that suit children's needs. From the research findings, it can influence students' understanding.